Cystic Fibrosis: Emergence of Highly Effective Targeted Therapeutics and Potential Clinical Implications - Mall, Marcus A. (Am J Respir Crit Care Med, 2020)
Cystic fibrosis (CF) remains the most common life-shortening hereditary disease in white populations, with high morbidity and mortality related to chronic airway mucus obstruction, inflammation, infection, and progressive lung damage. In 1989, the discovery that CF is caused by mutations in the CFTR (cystic fibrosis transmembrane conductance regulator) gene that encodes a cAMP-dependent anion channel vital for proper Cl(−) and HCO(3)(−) transport across epithelial surfaces provided a solid foundation for unraveling underlying disease mechanisms and the development of therapeutics targeting the basic defect in people with CF. In this review, we focus on recent advances in our understanding of the molecular defects caused by different classes of CFTR mutations, implications for pharmacological rescue of mutant CFTR, and insights into how CFTR dysfunction impairs key host defense mechanisms, such as mucociliary clearance and bacterial killing in CF airways. Furthermore, we review the path that led to the recent breakthrough in the development of highly effective CFTR-directed therapeutics, now applicable for up to 90% of people with CF who carry responsive CFTR mutations, including those with just a single copy of the most common F508del mutation. Finally, we discuss the remaining challenges and strategies to develop highly effective targeted therapies for all patients and the unprecedented potential of these novel therapies to transform CF from a fatal to a treatable chronic condition.